Design and Construction of Hybrid Autonomous Underwater Glider for Underwater Research - Simon Siregar; Bambang Riyanto Trilaksono; Egi Muhammad Idris Hidayat; Muljowidodo Kartidjo; Natsir Habibullah; Muhammad Fikri Zulkarnain; Handi Nugroho Setiawan (Robotics, 2023)
The main goal of this paper was to design and construct a hybrid autonomous underwater glider (HAUG) with a torpedo shape, a size of 230 cm in length and 24 cm in diameter. The control, navigation, and guidance system were executed simultaneously using a Udoo X86 minicomputer as the main server and three BeagleBone Black single-board computers as the clients. The simulations showed a controlled horizontal speed of 0.5 m/s in AUV mode and 0.39 to 0.51 m/s in glide mode with a pitch angle between 14.13<semantics>∘</semantics> and 26.89<semantics>∘</semantics>. In addition, the field experiments under limited space showed the proposed HAUG had comparable results with the simulation, with a horizontal speed in AUV mode of 1 m/s and in glide mode of around 0.2 m/s. Moreover, the energy consumption with an assumption of three cycles of gliding motion per hour was 51.63 watts/h, which enabled the HAUG to perform a mission for 44.74 h. The proposed HAUG was designed to hold pressure up to 200 m under water and to perform underwater applications such as search and rescue, mapping, surveillance, monitoring, and maintenance.